2021
DOI: 10.1002/lt.26188
|View full text |Cite
|
Sign up to set email alerts
|

Activated CD4+ T Cells and Highly Differentiated Alloreactive CD4+ T Cells Distinguish Operationally Tolerant Liver Transplantation Recipients

Abstract: Spontaneous operational tolerance to the allograft develops in a proportion of liver transplantation (LT) recipients weaned off immunosuppressive (IS) drugs. Several studies have investigated whether peripheral blood circulating T cells could play a role in the development or identify operational tolerance, but never characterized alloreactive T cells in detail due to the lack of a marker for these T cells. In this study, we comprehensively investigated phenotypic and functional characteristics of alloreactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, we ( 21 ) and others ( 17 , 20 ) have shown that a higher Vδ1/Vδ2 γδT-cell ratio is associated with CMV latency in LTx recipients. Recently, we also demonstrated that the Vδ1/Vδ2 γδT-cell ratio in peripheral blood does not differ between TOL and CTRL LTx recipients matched for CMV serostatus ( 30 ). Therefore it is likely that in these previous studies the tolerant group of LTx recipients harbored more CMV seropositive LTx recipients than the control or non-tolerant groups of LTx recipients.…”
Section: Discussionmentioning
confidence: 89%
“…However, we ( 21 ) and others ( 17 , 20 ) have shown that a higher Vδ1/Vδ2 γδT-cell ratio is associated with CMV latency in LTx recipients. Recently, we also demonstrated that the Vδ1/Vδ2 γδT-cell ratio in peripheral blood does not differ between TOL and CTRL LTx recipients matched for CMV serostatus ( 30 ). Therefore it is likely that in these previous studies the tolerant group of LTx recipients harbored more CMV seropositive LTx recipients than the control or non-tolerant groups of LTx recipients.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies examining peripheral blood circulating T cells in patients who achieved operational tolerance noted that activated (CD137-expressing), terminally differentiated alloreactive effector memory T helper (CD4) cells were hyperresponsive and circulating central and effector memory (CD4 + ) T helper cells were hyporesponsive to donor antigens and could discriminate operationally tolerant patients from other liver transplant recipients. 23…”
Section: Clinical Applications Of Biomarkersmentioning
confidence: 99%
“…7 Recent studies examining peripheral blood circulating T cells in patients who achieved operational tolerance noted that activated (CD137-expressing), terminally differentiated alloreactive effector memory T helper (CD4) cells were hyperresponsive and circulating central and effector memory (CD4 + ) T helper cells were hyporesponsive to donor antigens and could discriminate operationally tolerant patients from other liver transplant recipients. 23 Reduction in immunosuppression is often based on protocol rather than individualized assessment. Biomarkers allow for a more precise barometer of alloimmune activation enabling optimal timing and rate adjustment with immunosuppression minimization.…”
Section: Minimization Of Immunosuppressionmentioning
confidence: 99%
“…In the current issue of Liver Transplantation, Duizendstra et al have approached the analysis of donor-specific responses in spontaneous operational tolerance by employing an alternative in vitro assay in which antigen specificity is defined on the basis of the surface expression of the CD137 activation marker (also known as 4-1BB) following culture with donor or third-party cells. (10) These types of assay, known as activation-induced marker assays, are believed to be more sensitive and less biased toward specific T cell subpopulations than assays relying on T cell proliferation or cytokine production. Furthermore, they provide information at the single-cell level and allow detailed phenotypic characterization of antigen-specific cells using flow cytometry.…”
Section: See Article On Page 98mentioning
confidence: 99%
“…Beyond this, however, the interpretation of the findings of Duizendstra et al is not straightforward. (10) First, the confounding effect of immunosuppression cannot be completely eliminated by the inclusion of a cohort of nonimmunosuppressed healthy individuals. Second, the reduced proportion of alloantigen-specific memory CD4+ T cell subsets did not result in a reduced number of CD137+ interferon γ-producing CD4+ T cells (in which in vitro assays mostly correspond to memory CD4+ T cells).…”
Section: See Article On Page 98mentioning
confidence: 99%